2001
DOI: 10.1590/s0103-50532001000300012
|View full text |Cite
|
Sign up to set email alerts
|

Infraspecific variation in the chemistry of glandular trichomes of two Brazilian Viguiera species (Heliantheae; Asteraceae)

Abstract: Através do emprego da técnica de microamostragem de tricomas glandulares e análises por CLAE em sistema isocrático, foi efetuada a investigação química dos tricomas glandulares de diferentes populações de duas espécies de Viguiera. Nas seis amostras de V. robusta analisadas, o furanoeliangolido budleína A e seus isômeros contendo tiglato e metacrilato foram detectados como constituintes majoritários. Também foram detectados vários outros constituintes, na maioria em quantidades bem menores ou apenas traços. O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 4 publications
0
21
0
2
Order By: Relevance
“…(Pagni and Masini, 1999;Pagni et al, 2003), Stevia Cav. (Cornara et al, 2001), Tagetes L. (Poli et al, 1995), and Viguiera Kunth (Da Costa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…(Pagni and Masini, 1999;Pagni et al, 2003), Stevia Cav. (Cornara et al, 2001), Tagetes L. (Poli et al, 1995), and Viguiera Kunth (Da Costa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work (Da Costa et al, 1996), the STLs budlein A tiglate and atripliciolide tiglate were isolated from the crude extract of the leaves of V. robusta Gardn. Later, budlein A and its analogues were detected by HPLC in the glandular trichomes of the leaves of different populations of V. robusta (Da Costa et al, 2001). In this work, besides budlein A tiglate, we describe the isolation of large amounts of budlein A as well as the heliangolide niveusin A and a new eudesmanolide from the leaf rinse extract of V. robusta.…”
Section: Introductionmentioning
confidence: 87%
“…In A. robusta, the diterpenes manoyl oxide and manool, which belong to the labdanes class, were identified in the present study. Previous studies have identified heliangolides (Da Costa et al 2001) and diterpenes derived from kauranes (Da Costa et al 1996) in Aldama robusta (=Viguiera robusta).…”
Section: Monoterpenes Have Been Shown To Protect Against Herbivores Amentioning
confidence: 99%